Effects of biophilic virtual reality on cognitive function of patients undergoing laparoscopic surgery: study protocol for a sham randomised controlled trial - Bin Gao; Yanling Zhou; Jianhua Wang; Binbin Zhu; Qiuyan Weng; Wenjun Luo; Xiuchao He; Lufei Jin; Qinwen Wang; Ahmad Khaled Ahmad Harb (BMJ Open)
Introduction Virtual reality (VR) is already being used for cognitive or emotional rehabilitation. However, its role in postoperative cognitive dysfunction (POCD) has not been fully recognised. Due to the lack of an effective postoperative follow-up system, the incidence of POCD in China is not clear, and although many drugs have been proposed to improve POCD in the animal study, their clinical applications are limited, while VR provides an innovative method to provide non-pharmacological management.Methods and design This is a single-centre, randomised, double-blind, sham-controlled clinical trial. In this study, 600 patients over 55 years old undergoing laparoscopic surgery will be recruited. Participants will be randomly assigned to receive biophilic VR or sham VR (1:1 ratio), all patients have 20 min of exposure per day during the hospital stay. The primary outcome is the impact of VR on the incidence of POCD. Secondary outcomes include perioperative anxiety and instrumental activities of daily living. Changes in the performance of the neurocognitive batteries are measured by a local resident doctor. Serum samples will be collected on the day before surgery and 7 days after surgery.Ethics and dissemination This trial has ethical approval from the Medical Ethics Committee of the Affiliated Hospital of Medical School of Ningbo University (KY20210302). The study is sponsored by Ningbo University and Ningbo Science and Technology Bureau. Contact: Dr. Mao Haijiao, Chair of the hospital medical Ethics committee (ndfylunli@126.com). Trial results will be submitted for publication in peer-reviewed journals, patient recruitment began in April 2021. Written informed consent is obtained for all participants. All information acquired will be disseminated via national or international conferences and published in peer-reviewed journals.Trial registration number ChiCTR2000040919.